Conception rates in early postpartum ewes bred naturally or by intrauterine insemination - Warren, Jr, J E; Kiesling, D O; Akinbami, M A; Price, E A; Meredith, S (Journal of animal science, 1989)
Ewes were treated with a medroxyprogesterone acetate (MAP) sponge for 8 d followed, at sponge removal, with 500 IU pregnant mare serum gonadotropin (PMSG) at d 30, 40 or 50 (d 0 = lambing) to induce estrus. Dry and lactating ewes were divided into equal numbers at each postpartum day and bred at estrus. Conception rates and number of accessory sperm were determined by flushing the oviducts 3 d after mating and examining the recovered ova. There was no effect (P greater than .05) of lactational status on conception rates. Conception rates increased (P less than .05) from d 30 (10%) to d 40 (45%) and from d 40 to d 50 (80%). There were fewer (P less than .05) ova with accessory sperm (5/26) in d-30 ewes compared with d-40 (10/27) or d-50 (12/24) ewes. In Exp. 2, ewes were assigned to two groups after receiving PMSG on d 30: 1) mated naturally or 2) inseminated during laparotomy near the uterotubal junction (UTJ). Dry and lactating ewes were divided evenly within each of the two treatments. Oviducts were flushed and ova were examined for cleavage. The conception rate was 60% in ewes that were inseminated in the UTJ vs 10% in ewes mated to rams (P less than .05). Lactational status had no effect on results. In conclusion, conception rates in postpartum ewes treated with MAP sponge and PMSG increased from postpartum d 30 to d 50 with natural breeding, and d-30 conception rates were increased over natural mating by insemination into the uterine horn near the UTJ.